2013
DOI: 10.1007/s13197-013-1239-9
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical properties of gelatin from bighead carp (Hypophthalmichthys nobilis) scales by ultrasound-assisted extraction

Abstract: In this study, gelatin was extracted from bighead carp (Hypophthalmichthys nobilis) scales by water bath (WB) and ultrasound bath (UB) at 60°C for 1 h, 3 h and 5 h, named WB1, WB3, WB5, UB1, UB3 and UB5, respectively. The physicochemical properties of gelatin were investigated. The result indicated that gelatin extracted from bighead carp scales had a high protein content (84.15~91.85 %) with moisture (7.111 3.65 %), low ash content (0.31~0.97 %). All extracted gelatin contained α-and β-chains as the predomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 53 publications
2
63
0
3
Order By: Relevance
“…[42] The amide II band in the infrared spectrum of protein is in the range of 1600-1500 cm −1 [5] which primarily represent an out-of-phase combination of CN stretch and in-plane NH deformation modes of the peptide group. [41] In this study, the characteristic absorption value of modified OVA in amide-II region was slightly highest than those of native and hydrolyzed OVA (data not shown). It has also reported that Amide A band of the infrared spectra of polymer is observed at an unusually high frequency (3400-3300 cm −1 ), which was related to hydrogen bond stretching and the vibration of OH groups.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…[42] The amide II band in the infrared spectrum of protein is in the range of 1600-1500 cm −1 [5] which primarily represent an out-of-phase combination of CN stretch and in-plane NH deformation modes of the peptide group. [41] In this study, the characteristic absorption value of modified OVA in amide-II region was slightly highest than those of native and hydrolyzed OVA (data not shown). It has also reported that Amide A band of the infrared spectra of polymer is observed at an unusually high frequency (3400-3300 cm −1 ), which was related to hydrogen bond stretching and the vibration of OH groups.…”
Section: Resultsmentioning
confidence: 53%
“…[40] Amide-I represents C = O stretching vibration hydrogen bonding coupled with COO, coupled to contributions from the CN stretch, CCN deformation and in-plane NH bending mode. [40,41] As shown in Fig. 4(b), the amide I absorption peaks of native OVA, hydrolyzed OVA and modified OVA were 1660.2, 1654, and 1651 cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 90%
“…Lately, fish scale has been focused as an ideal source for collagen and gelatin extraction Fengxing et al 2008;Yong-an and Jing-na 2010;Zhang et al 2011;Mori et al 2013;Tu et al 2015). Akagunduz et al (2014) reported higher yield and bloom strength values for gelatin extracted from scales compared to that from bones in sea bream.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we extracted FSG from bighead carp (Hypophthalmichthys nobilis) scales and reported its physical-chemical properties and structural characteristics (Sha et al 2014;Tu et al 2015). Nevertheless, there is no information regarding modifying bighead carp scales gelatin.…”
Section: Introductionmentioning
confidence: 99%